Antimicrobial Resistance and Molecular Typing of Stenotrophomonas Maltophilia Clinical Isolates from Hospital Kuala Lumpur - Rauhani Rankouhi, Seyedeh Zahra (2011)
Stenotrophomonas maltophilia (S. maltophilia) is an emerging pathogen, is now recognized as an important cause of hospital acquired infection, causing significant morbidity and mortality especially among immunocompromised patients. S. maltophilia cause a wide variety of diseases such as cystic fibrosis, bacteremia, pneumonia, urinary tract infection, surgical site infection, and peritonitis. The lack of proper laboratory diagnosis system and its intrinsic resistance to a plethora of antimicrobial agents that severely limit commonly used empiric standard antimicrobial therapies makes S. maltophilia a great challenge in the clinical setting. In Malaysia, the rate of S. maltophilia isolation has increased over the recent years with more than 100 cases in Hospital Kuala Lumpur (HKL) since the year 2003. Therefore, the present study was aimed at developing a selective culture media for the fast and accurate isolation of S. maltophilia that can be routinely used in diagnostic laboratory and to determine the antibiotic resistance mechanism and molecular epidemiology of local clinical isolates. In this study, a total of hundred S. maltophilia isolates were collected from HKL from January to December 2008, of which only 64 were available for the study, since most of the remaining isolates either failed to grow or were contaminated or were not confirmed as S. maltophilia. In order to develop a selective culture media for S. maltophilia isolation, media such as modified mannitol agar and MacConkey agar was prepared with the addition of antibiotics such as vancomycin, mereopenem and mphoterecin. In addition modified DNase toluidine-blue agar (mDTBO) which is a chromogenic medium that specifically selects S. maltophilia with an additional property of DNase production was formulated in the present study. All these methods were compared with a previously mVIA mthod.Evaluation of the mDTBO with 64 S. maltophilia isolates and a panel of gram negative and gram positive bacteria showed 100% specificity and 75% sensitivity. The reason for reduced sensitivity when queried through DNase tube test, it was found that, some strains produced DNase after 48 hours and few did not produce DNase. From this study,it is found that mDTBO is a fast and accurate isolation media for S. maltophilia, however, isolates that show negative result on agar plate but having a positive clinical implication need to be confirmed by DNase tube test. Compared to mDTBO, mVIA is more selective with 98% sensitivity. Among the four methods compared for the isolation of S. maltophilia mVIA agar gave maximum sensitivity compared to blood agar,MacConkey agar and mDTBO agar. Resistance is usually mediated by sul1, sul2 genes carried by integrons or plasmids. The antibiotic susceptibility pattern and the genes coding for sul1, sul2, and class I and class II integrons are investigated in the Malaysian isolates. Of the 64 isolates tested, one isolate (1.56%) showed resistance (MIC > 32 mg/L) to TMP/SMX which possessed sul1 gene and carried the class I integron. None of the isolates carried sul2 or class 2 integron. All isolates were 100% resistant to meropenem, imipenem and piperacillin/tazobactam. All S. maltophilia isolates were susceptible to Minocycline (MH). This study presents the first report on TMP/SMX resistance in S. maltophilia in Malaysia. Since TMP/SMX is the mainstay therapy for S. maltophilia infection, monitoring its resistance is important, as it has the potential to increase by means of mobile elements. As from the current study, the antibiotic minocycline is found to be promising with 100% susceptibility towards S. maltophilia, it is recommended for consideration. To determine the epidemiology of S. maltophilia in the largest tertiary care hospital in Malaysia (HKL), 63 isolates were genotyped by Pulsed Field Gel Electrophoresis (PFGE) technique using the SpeI restriction endonuclease enzyme. Analysis of the PFGE banding patterns by ioNumerics 6.1 software yielded 58 distinct patterns,including 5 clusters of patterns with 100% and 3 clusters with over 80% similarity.Some isolates that showed close relatedness were isolated from the same patient (isolates 2 and 3, 6 and 7), but in some cases, isolates were from different patients,sources and wards (55 and 12, 1 and 50, 41 and 46). In some cases, strains isolated from the same patients were genetically distinct. The results from PFGE analysis indicate that S. maltophilia isolates are genetically diverse and polyclonal emergence is possible, but person to person transmission of strains across the ward is not common. In conclusion, this study has developed an mDTBO media for the fast and correct isolation of S. maltophilia however mVIA with better sensitivity is more suitable for routine use in diagnostic labs. Current study reports the first TMP/SMX resistant S. maltophilia in Malaysia. The epidemiological investigation has shown that S. maltophilia strains are genetically diverse with possible polyclonal emergence. Prompt diagnosis, early treatment with appropriate drugs and epidemiological monitoring across the country is crucial for the effective management of this rapidly emerging nosocomial pathogen S. maltophilia.